Multi-Grade Teaching and Inclusion: Selected Cases in the Free State Province of South Africa - Makoelle, Tsediso; Malindi, M. J. (International Journal of Educational Sciences, 2014)
Multi-grade teaching is a commonly used pedagogic strategy in rural schools. However, this form of teaching continues to present challenges to both the teacher and the learner in particular since the advent of inclusive education in South Africa. The policy on inclusive education is silent on how it could be enhanced in a multi-grade class. This paper therefore attempts to analyse and deconstruct the tensions, contradictions and anomalies within the practice of inclusion as a pedagogic discourse in a multi-grade teaching system. The qualitative study on which this article is based employed a critical emancipatory lens and critical realist analysis as instruments with which to analyse narratives from selected cases at multi-grade schools in the Free State province of South Africa. The findings of the study indicated that, while the knowledge and skills teachers need to enhance inclusion within a multi-graded system were limited, well-designed teaching practices in a multi-grade class may enhance an inclusive pedagogy and promote inclusive learning.
Keywords: inclusion; inclusive pedagogy; Integration; Mainstreaming; multi-grade teaching